Farmers perception about risks related with irrigation residual water use in Atlixco, Puebla - Téllez Pérez, Victoria; Ocampo Fletes, Ignacio; Tornero Campante, Mario Alberto; Antonio López, Pedro; Villarreal Manzo, Luis Alberto; Mendoza Hernández, José Carlos (Acta Universitaria, 2023)
The objective was to know the perception of farmers about the risk of using residual water in agricultural activities in the upper area of Atlixco, Puebla. A survey was applied to 48 farmers who use water from the Atoyac River, rating means were generated on a scale of 1 to 4 to know the magnitude of the perceived risks, and the Fisher’s exact test (p ≤ 0.05) was used for the association between variables. Results show that 50% of the farmers rated the problem as very serious, 100% observed changes in the color of the soil, and 68.8% qualified water as undesirable due to its color and 60.4% due to its bad odor. In crops, 73.0% observed rotting, wilting, drying, and pests; 72.0% reported better crops; and 54.2% detected damage to their health. Farmers recognize negative effects on soil, crops, and humans, but they consider they are not of high risk.